Exploring the perspectives of people who use drugs living with hepatitis C on interactions with case managers: A qualitative study in Taiwan - Pei Chen Hsu; Hung-Chi Wu; Wan-Ling Chen; Jing-Jy Wang (Belitung Nursing Journal, 2026)
Background: Comorbidity treatment for people who use drugs with hepatitis C should be integrated with addiction treatment. Case management plays a crucial role in enhancing treatment motivation and improving treatment completion rates. Previous studies have focused on outcomes, disease, or treatment experiences. However, studies exploring the perspectives of people who use drugs living with hepatitis C on their interactions with case managers remain limited. Objective: To explore the perspectives of people who use drugs with hepatitis C receiving case management services on their interactions with case managers. Methods: This exploratory qualitative study was conducted in a psychiatric hospital in southern Taiwan that provides addiction treatment services for individuals with substance use disorders. Purposive sampling was used to recruit participants who had received case-managed HCV treatment and completed the full course of care. Semi-structured, in-depth interviews were conducted with nine participants in a private space within the hospital’s outpatient clinic between September 2022 and December 2023 and analyzed using a qualitative content analysis. Results: Four themes were identified: (a) feeling empowered through respectful communication and shared decision-making, (b) transformation in health literacy and understanding of hepatitis C, (c) increased engagement in treatment facilitated by case management support, and (d) Diverse views of the importance of case managers’ professional backgrounds. These perspectives reflected how case-managed HCV care shaped participants’ experiences and engagement, underscoring the essential role of communication, education, and supportive relationships within addiction treatment settings. Conclusion: The findings of this study highlight patients’ perspectives on addiction case management and underscore the importance of trust-based communication, continuity of care, and tailored education in enhancing engagement in HCV care. These results provide practical implications for developing core competencies among addiction case managers in addressing the comorbidities of substance use and hepatitis C.